Designing ERT APPS (E-Reading Text) for Senior High School - Luluk Choirun Nisak Nur; Siti Mukarromah; Nurul Afidah (SCHOOLAR: Social and Literature Study in Education, 2021)
This research is aimed to design a learning media that called ERT Apps (E-Reading Text) for Senior High School, especially in reading skill material. This research discusses the media for learning reading skill based on Power Point Hyperlink as a media to support teaching and learning activities. This research uses Research & Development methods with ADDIE models which consist of five stages such as Analysis, Design, Development, Implementation, and Evaluation. The subject of research are the eleventh grade students in MA Unggulan KH. A. Wahab Hasbullah Tambakberas Jombang. This researcher uses questionnaires and interviews as a way of collecting data to get a response from the product. The ERT Apps (E-Reading Text) product was validated by two experts, namely, media expert and material expert before being tested on students Based on the results of the validation, the score of this product by media experts is 3.11 and the score of material experts is 4.35. The implementation score is 4.46 The score is categorized as "Good". In conclusion of this research states that students are interested in learning English by using ERT Apps (E-Reading Text) as a learning media. Keywords: ERT Apps, Senior High School, Reading Skill.